The value of Acacia saligna as a source of fodder for ruminants - Howard, Delwyn M. (Curtin University, 2002)
Three pen trials were conducted to evaluate the value of A. saligna as a source of feed for ruminants. In Trial 1 A. saligna was inadequate as the sole source of nutrients for sheep. Furthermore, the level of detannification achieved in Trial 1, with the addition of PEG 4000 or PEG 6000, failed to improve the diet sufficiently. The antinutritional effects on the animals were largely attributed to the excessive biological activity of the phenolics in the A. saligna leaves. Feeding of these leaves, without PEG, had a definite defaunating effect on the ruminal fluid. The ruminal ammonia levels were all well below the threshold for maximal microbial growth. Given the results of Trial 1, the second trial was undertaken to determine if A. saligna was more useful as a supplement rather than a basal diet. The benefits of including A. saligna as a supplement to a basal diet of lupins and wheat straw were not clear. The benefits of including a detannification agent with the A. saligna were also not evident. Ruminal ammonia levels were much higher than in Trial 1 and animals generally maintained weight. Trial 2 revealed that the sheep were capable of consuming significantly more A. saligna than they did in Trial 1, but it was not clear whether this was due to the basal diet providing adequate nutrients or if it was due to differences in the A. saligna fed in the respective trials. Total phenolics, CT and PPC were considerably lower than those of Trial 1. Trial 3 was designed to investigate the use of A. saligna as the basal source of nutrients, with or without a supplement of N in the form of urea or PEG. Total phenolics, CT and PPC were lower than those of Trial 1, but higher than those of Trial 2. Animals consumed more A. saligna than in Trial 2 and generally maintained weight.The results from Trial 3 suggest that A. saligna could be a useful feed source for ruminants. The substitution of straw with A. saligna indicates that its incorporation into a grazing system could significantly decrease grazing pressure on dry summer pastures. In Trial 3 goats were not shown to have a superior ability than sheep in utilising A. saligna as a source of nutrients.